Historians of Asia on Political Violence - Cheng, Anne; Kumar, Sanchit (Institut des civilisations, 2021)
In the general opinion, Asia as a whole tends to be represented (and more often than not, to represent itself) as devoid of violence: look at Indian "non-violence", Chinese Taoist "non-action", Confucian "harmony", Buddhist "love for peace" or Japanese "Zen philosophy"... This may fill the shelves of "Oriental wisdom" sections in our bookshops, but most historians do not buy into this kind of "feel good" projections and are acutely aware that any society whatsoever, wherever it is located, teems with violence, and that violence is part and parcel of any kind of polity. Furthermore, the political violence which is the topic of this volume is not just about war, it can take on very diverse forms, including, as will be shown by some of the articles presented here, iconic vandalism, distorted modes of interpretation, warped forms of ideological discourse, collective amnesia and negationism. The present volume is the second of the "Myriades d'Asies" series inaugurated with India-China: Intersecting Universalities. Just as the preceding one, it is a collection of articles resulting from an international conference organised by the Chair of Chinese Intellectual History in June 2019. As a reflection of the Collège de France spirit of public service intent on making knowledge available to all for free, all the volumes of the series are published online and in open access. Our hope is that these articles, written by eminent historians of Asia and from very different viewpoints which cut across vast expanses of time and space, will lead readers and researchers alike to reflect further on the multiple faces of political violence, as well as their infinite complexities, so as to avoid giving in to ideological and judgmental binaries that are the common junk food for non-thought. This seems to be increasingly essential today since the 21st century is supposed to be the century of Asia.